B. Bronchiseptica empyema necessitans, a case report - Samantha Wray; Nikko Rowe A. Tabliago; Richard Lueking (BMC Pulmonary Medicine)
Abstract Background Empyema necessitans is an uncommon complication of an empyema, where pus in the pleural cavity extends into the chest wall. Both medical and surgical management are required. Here we have identified the first reported case of empyema necessitans caused by Bordetella bronchiseptica. Case presentation A 60-year-old female dog trainer initially presented with a right chest wall lesion. Imaging showed a right-sided empyema and chest wall fistulization. Multiple Gram stains and cultures isolated Bordetella bronchiseptica. After several courses of antibiotics, imaging showed a chronic pleural collection with communication to a chest wall gas-fluid collection resembling empyema necessitans. Culture re-demonstrated Bordetella bronchiseptica. She was given a six-week course of oral moxifloxacin and underwent a Clagett window. Conclusions While Bordetella bronchiseptica has been previously exclusive to animals, it is an emerging zoonosis. Empyema necessitans because of repeated animal exposure is an unusual complication that had yet to be seen with this microorganism.